2017
DOI: 10.1111/icad.12277
|View full text |Cite
|
Sign up to set email alerts
|

Rush hours in flower visitors over a day–night cycle

Abstract: Most research on pollination has focussed on a subset of insect taxa within a narrow time window during daylight hours. As a consequence, we have a limited understanding of the diversity and activity of flower visitors during the night or belonging to taxa other than bees or syrphid flies. Here, we quantified the abundance and species richness of flower visitors in ruderal meadows over repeated 24‐h cycles (i.e. day and night), and identified abiotic factors influencing these patterns. From the plant perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 44 publications
1
36
3
Order By: Relevance
“…As found elsewhere (Fijen and Kleijn , Knop et al. ), prior studies in the study area have shown that abundance and diversity of insect pollinators declined considerably in the afternoon (Herrera , ; personal observations ), and there was no evidence of crepuscular or nocturnal pollination for any of the plant species studied here. In addition, flowers of about one‐third of the species studied are not available to pollinators in the afternoon, since their corollas whither (e.g., Asphodelus , Hypericum , Urginea ), close (e.g., Campanula , Catananche , Chondrilla ), or fall (e.g., Cistus , Helianthemum , Linum ) shortly after noon.…”
Section: Methodssupporting
confidence: 84%
“…As found elsewhere (Fijen and Kleijn , Knop et al. ), prior studies in the study area have shown that abundance and diversity of insect pollinators declined considerably in the afternoon (Herrera , ; personal observations ), and there was no evidence of crepuscular or nocturnal pollination for any of the plant species studied here. In addition, flowers of about one‐third of the species studied are not available to pollinators in the afternoon, since their corollas whither (e.g., Asphodelus , Hypericum , Urginea ), close (e.g., Campanula , Catananche , Chondrilla ), or fall (e.g., Cistus , Helianthemum , Linum ) shortly after noon.…”
Section: Methodssupporting
confidence: 84%
“…bees, may visit other sympatric flowering plants over the course of their lifetime [5]) [6]. Additionally, recent work suggests that many generalist flowers are visited nocturnally as well as during the day [7]. Despite these facts, nocturnal pollinators have been less frequently studied (Table 1), and may therefore be undervalued.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the total number and species of flower-visiting insects within each sampling point, data from both methods were pooled together. Only active flower-visiting insects, defined as any insect that intentionally moved in or on an inflorescence thereby touching the reproductive organs of the flower (Knop et al 2018), were included. The total number of P. brevis adults and immatures inside the hoop was counted and we took note of whether the katydid was on a flower or on the leaves.…”
Section: Methodsmentioning
confidence: 99%
“…material 1 for the details and explanation of each proposed model). Each model contained a different combination of the following predictors: 1) abundance of all flower-visiting insects, 2) abundance of ambush predator crab spiders, 3) abundance of main competitors (bees, see Lindström et al 2016), 4) presence or absence of ants, 5) time period of sampling (see Knop et al 2018), 6) total flower abundance, and 7) plant species richness. We ensured that all models were biologically meaningful and not overfitted.…”
Section: Methodsmentioning
confidence: 99%